Tumescent mastectomy: the current indications and operative tips and tricks - Khater A (Dove Medical Press, 2017)
Ashraf Khater,1 Alaa Mazy,2 Mona Gad,2 Ola Taha Abd Eldayem,2 Mohamed Hegazy1 1Department of Surgical Oncology, Mansoura Oncology Center (OCMU), 2Anesthesia and Surgical Intensive Care Department, Mansoura University Hospital, Faculty of Medicine, Mansoura University, Mansoura, Egypt Background: Tumescent mastectomy refers to usage of a mixture of lidocaine and epinephrine in a diluting saline solution that makes flaps firm and tense, thus minimizing systemic drugs toxicity and making surgery possible with minimal bleeding. This technique is very useful in elder women and those with American Society of Anesthesiologists; score III and IV. The objective was to establish an alternative safe technique to general anesthesia in some selected mastectomy patients.Patients and methods: Twenty candidate women for total mastectomy and axillary dissection were enrolled and consented to participate. After preparation, an anatomically directed infiltration was made under sedation, using a cocktail of lidocaine, bupivacaine, and epinephrine, followed after 20 minutes by the surgical incision and completion of mastectomy. All intraoperative and postoperative outcomes were recorded.Results: Although 7 cases required added analgesic medications, no conversion for general anesthesia was recorded. Mean operative time was 81±15.8 minutes. Mean blood loss was 95.8±47.5 mL. There was no recorded intraoperative hemodynamic instability. Postoperative visual analog score was not exceeding 4 till the end of the first 24 hours. Opioids were not required in any case, and the mean dosage of Ketorolac used was 30±8.75 mg. Drains output and the incidence of postoperative complications were acceptable.Conclusion: We can consider tumescent mastectomy in well-selected patients a safe alternative for performing mastectomy when general anesthesia is hazardous, with minimal blood loss and long lasting postoperative analgesia without an additive effect on the operative time, hospital stay, and intraoperative and postoperative complications. Keywords: tumescent, mastectomy, anesthesia, lidocaine